KAJIAN KERUSAKAN DAN STRATEGI PENGELOLAAN TERUMBU KARANG DI KAWASAN KONSERVASI LAUT DAERAH (KKLD) GILI SULAT DAN GILI LAWANG LOMBOK TIMUR NUSA TENGGARA BARAT - Subhan, Ahmad; Ardhana, I.P.G; Wiryatno, Joko (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 8 No 1 (2014), 2014)
Coral reef and its life within is a high value natural resources. Management of KKLD GiliSulat-GiliLawas has been going for 8 years, however the management was still not maximal, in particular on preservation of coral reef ecosystem in the conservation area, and community commitment in managing and conserving fish resources and other biota. Therefore, to improve management planning, study need to be done with the aim to find out destruction level of coral reef at KKLD GiliSulat – GiliLawang, based on coverage percentage, fishermen, private sector and government perception. Also to identify policy related with coral reef management in this area, then to formulate its management strategies. Results of the survey shows that in general, average condition of the coral reef in this area is fair ( lifeform = 49,26%). Recommended management strategies in KKLD GiliSulat-GiliLawang include SO strategies ( Strength - Opportunity ) which are coral reef management should be based on ecotourism, increasing community involvement in managing the coral reed and improve institutional strength of KPPL, and maximizing function and task of UPTD KKLD. WO strategies ( Weakness - Opportunity ) are increasing monitoring, give training on coral reef conservation, improving partnership in management, and increasing quality and quantity of KKLD human resources. ST strategies are ( Strength – Threats ) socialization of regulation, increasing effective coordination among stake holder, accurate analysis of environmental impact and improve research and sustainable diversification on fishing businesses. WT strategies are ( Weakness- Threats) compliance to law, involving all parties in every decision made and making a good coastal areas plan.
Keywords: Marine conservation, coral reef, GiliSulat-GiliLawang